Hubungan Riwayat ASI Eksklusif, Riwayat Pemberian MP-ASI, dan Pendidikan Ibu dengan Stunting pada Anak 12-36 Bulan di Puskesmas Sidotopo Surabaya - Hasna Izdihar; Arian Susanti Dewi Cahyani; Lailatul Muniroh (Universitas Airlangga, 2023)
Background: Stunting is one of the main health problems in Indonesia which is associated with an increased risk of disease, mortality, and a suboptimal brain development. The prevalence of stunting in East Java is 33,6% (above the national prevalence). Semampir District has a total of 1.399 stunting cases. Exclusive breastfeeding, appropriate complementary feeding, and maternal education can contribute to supporting child's health that can help prevent stunting. Objectives: This study aims to analyze the relationship between a history of exclusive breastfeeding, a history of complementary feeding and maternal education with stunting in children age 12-36 months in the working area of the Sidotopo Public Health Center Surabaya. Methods: This study was a cross sectional design with simple random sampling. The sample size were 78 children age 12-36 months in the Sidotopo Public Health Center working area. The instrument used was a questionnaire. Data analysis using Chi-square test. Results: The results showed that there was no significant relationship between the history of exclusive breastfeeding (p=0.121), complementary feeding (p=0.185) and maternal education (p=0.919) with stunting in children 12-36 months, but most stunted children had a history of non-exclusive breastfeeding (44.4%), came from mothers with low education levels (36.9%) and had a history of inappropriate complementary feeding (42.3%). Conclusions: There were many determinants of stunting in children, not only caused by exclusive breastfeeding, the pattern of complementary feeding, and maternal education, but also caused by factors such as birth weight, maternal nutritional status, birth length, hygiene and sanitation, and others.